COMPASS-CP: An Electronic Application to Capture Patient-Reported Outcomes to Develop Actionable Stroke and Transient Ischemic Attack Care Plans. Issue 8 (August 2018) - Duncan, Pamela W.; Abbott, Rica M.; Rushing, Scott; Johnson, Anna M.; Condon, Christina N.; Lycan, Sarah L.; Lutz, Barbara J.; Cummings, Doyle M.; Pastva, Amy M.; D'Agostino, Ralph B.; Stafford, Jeanette M.; Amoroso, Robert M.; et al.
Abstract : Background: Patient-reported outcomes (PROs) are clinical tools that measure patients' goals of care and assess patient-reported physical, mental, and social well-being. Despite their value in advancing patient-centered care, routine use of PROs in stroke management has lagged. As part of the pragmatic COMPASS (Comprehensive Post-Acute Stroke Services) trial, we developed COMPASS-Care Plan (CP), a clinician-facing application that captures and analyzes PROs for stroke and transient ischemic attack patients discharged home and immediately generates individualized electronic CP. In this report, we (1) present our methods for developing and implementing COMPASS-CP PROs, (2) provide examples of CP generated from COMPASS-CP, (3) describe key functional, social, and behavioral determinants of health captured by COMPASS-CP, and (4) report on clinician experience with using COMPASS-CP in routine clinical practice for care planning and engagement of stroke and transient ischemic attack patients discharged home. Methods and Results: We report on the first 871 patients enrolled in 20 North Carolina hospitals randomized to the intervention arm of COMPASS between July 2016 and February 2018; these patients completed a COMPASS follow-up visit within 14 days of hospital discharge. We also report user satisfaction results from 56 clinicians who used COMPASS-CP during these visits. COMPASS-CP identified more cognitive and depression deficits than physical deficits. Within 14-day posthospitalization, less than half of patients could list the major risk factors for stroke, 36% did not recognize blood pressure as a stroke risk factor, and 19% of patients were nonadherent with prescribed medications. Three-fourths of clinicians reported that COMPASS-CP identifies important factors impacting patients' recovery that they otherwise may have missed, and two-thirds were highly satisfied with COMPASS-CP. Conclusions: The COMPASS-CP application meets an immediate need to incorporate PROs into the clinical workflow to develop patient-centered CP for stroke patients and has high user satisfaction. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02588664. Abstract : Supplemental Digital Content is available in the text.